Ion‐Selective Prussian‐Blue‐Modified Celgard Separator for High‐Performance Lithium–Sulfur Battery. Issue 18 (1st August 2018) - Wu, Xian; Fan, Lishuang; Qiu, Yue; Wang, Maoxu; Cheng, Junhan; Guan, Bin; Guo, Zhikun; Zhang, Naiqing; Sun, Kening
Abstract: Application of Li–S batteries has been restricted because of their major problem, that is, shuttling of soluble polysulfides between electrodes, which results in serious capacity fading. For the development of high‐performance Li–S batteries, we first time utilize a simple growth method to introduce a Prussian blue (PB)‐modified Celgard separator as an ion‐selective membrane. The unique structure of PB could effectively suppress the shuttle of polysulfides but scarcely affect the transfer ability of lithium ions, which is beneficial to achieve high sulfur conversion efficiency and capacity retention. The Li–S battery with PB‐modified Celgard separator has an average capacity decay of only 0.03 % per cycle at 1 C after 1000 cycles. Abstract : Li—pass, S—no chance : An ion‐selective and cheap separator is required to construct high‐performance lithium–sulfur batteries. To address the problem, a Celgard separator modified with Prussian blue is prepared through a simple growth method. This innovative separator allows unhindered diffusion of Li ions but hinders diffusion of polysulfides without affecting the performance.